Web-Based Village Potential Information Management in Agung Timur Village - Hartati, Sri; Rifkiyandi, Daffa (JLASA (Journal of Law and State Administration), 2023)
This study aims to analyze the implementation of Web Government-based Village Potential Information Governance in Agung Timur Village. The findings indicate that the system has improved transparency, administrative efficiency, and information accessibility for the local community. The use of information technology has accelerated accurate and structured data collection of village potentials while encouraging active community participation in development. However, challenges remain in terms of limited internet infrastructure and the digital literacy of village officials. Referring to previous studies, this implementation is considered successful, although continuous improvement in human resources and infrastructure support is necessary to ensure optimal and sustainable system performance.